Characteristics of Indigenous Bacterial Isolates from Cocoa Plantations in Meko Village, Central Sulawesi, with Ability to Degrade Cellulose - Anak Agung Sagung Putri Risa Andriani; Widyatmani Sih Dewi; Novizar Nazir; Ni Luh Putu Putri Setianingsih; Eko Rini Indrayatie; Kalimutu, Krisnawan (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
The characteristics of indigenous bacterial isolates in cocoa farms differ based on the study's location and methodology. More research is required to comprehend these bacterial isolates' diversity and features completely. This study intends to assess the cellulose-degrading capacity of bacterial isolates from cocoa plantations in Meko Village, Central Sulawesi. The shape of the bacterial colony, the shape of the colony's edge, elevation, colony size, color, and texture are considered during macroscopic morphological identification and microscopic morphological identification after gram stain. Afterward, gram stains the bacteria to determine the type of cell wall. Hydrolysis capacity was then identified macroscopically by observing colony shape, colony periphery, colony color, colony appearance and height, and hydrolysis capacity on media in a petri dish (HC). Upon microscopic examination of cell shape and bacterial wall type (Gram-positive and gram-negative). Based on the research findings and identification of bacteria capable of degrading cellulose in cocoa soil, it can be inferred that among the 28 examined isolates, six isolates have the greatest HC index values in KL62 isolates. In contrast, GL66, KL23, and KL62x isolates have medium HC index values.